Multistage Fragmentation of Ion Trap Mass Spectrometry System and Pseudo-MS3 of Triple Quadrupole Mass Spectrometry Characterize Certain (E)-3-(Dimethylamino)-1-arylprop-2-en-1-ones: A Comparative Study - Ali S. Abdelhameed; Adnan A. Kadi; Hatem A. Abdel-Aziz; Rihab F. Angawi; Mohamed W. Attwa; Khalid A. Al-Rashood (The Scientific World Journal)
A new approach was recently introduced to improve the structure elucidation power of tandem mass spectrometry simulating the MS3 of ion trap mass spectrometry system overcoming the different drawbacks of the latter. The fact that collision induced dissociation in the triple quadrupole mass spectrometer system provides richer fragment ions compared to those achieved in the ion trap mass spectrometer system utilizing resonance excitation. Moreover, extracting comprehensive spectra in the ion trap needs multistage fragmentation, whereas similar fragment ions may be acquired from one stage product ion scan using the triple quadrupole mass spectrometer. The new strategy was proven to enhance the qualitative performance of tandem mass spectrometry for structural elucidation of different chemical entities. In the current study we are endeavoring to prove our hypothesis of the efficiency of the new pseudo-MS3 technique via its comparison with the MS3 mode of ion trap mass spectrometry system. Ten pharmacologically and synthetically important (E)-3-(dimethylamino)-1-arylprop-2-en-1-ones (enaminones 4a–j) were chosen as model compounds for this study. This strategy permitted rigorous identification of all fragment ions using triple quadrupole mass spectrometer with sufficient specificity. It can be used to elucidate structures of different unknown components. The data presented in this paper provide clear evidence that our new pseudo-MS3 may simulate the MS3 of ion trap spectrometry system.